Incidence, risk factors, and outcomes of jejunal varix of the afferent loop after pancreatoduodenectomy. Issue 12 (December 2022) - D'Silva, Mizelle; Yoon, Yoo-Seok; Lee, Jun Suh; Cho, Jai Young; Lee, Hae Won; Lee, Boram; Kim, Moonhwan; Han, Ho-Seong
Abstract: Background: Jejunal varix is a concerning late complication after pancreatoduodenectomy (PD) due to the risk of recurrent and intractable bleeding. Our aim was to investigate the incidence, risk factors, and outcomes of jejunal varix after PD. Methods: A total of 709 patients who underwent PD between 2007 and 2017 were included. Preoperative and postoperative CT images were reviewed to evaluate the development of portal vein (PV) stenosis (≥50%) and jejunal varices. Results: Jejunal varix developed in 83 (11.7%) patients at a median of 12 months after PD. Eighteen (21.7%) patients experienced variceal bleeding. PV stenosis ( P < 0.001; odds ratio [OR] 33.2, 95% confidence interval [CI] 15.6–66.7) and PV/superior mesenteric vein resection ( P = 0.028; OR 2.3, 95% CI 1.1–4.7) were independent risk factors for jejunal varix. Of the nine patients who underwent stent placement for PV stenosis before the formation of jejunal varices, none experienced variceal bleeding. By contrast, 18 (27.3%) of the 135 patients without PV stent placement experienced at least one episode of variceal bleeding. Conclusions: The incidence of jejunal varix was substantial after PD. PV stenosis was a strong risk factor for jejunal varix. Early PV stent placement and maintaining stent patency could reduce the risk of variceal bleeding in patients with PV stenosis.